Narrative Economics and Intersubjective Fiction: The Construction of Bitcoin Finfluencer Discourse on YouTube Social Media in Indonesia - Deri Hudaya; Haryadi Mujianto; Muhamad Hilman Firmansyah (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2026)
This study analyzes the narrative construction of Bitcoin on Angga Andinata's YouTube channel through two sample videos representing opposing market phases: Halving 2024: Ini Jalan Ninjaku (bull market phase) and Bocoran Bottom Bitcoin 2026 (bear market phase). Integrating Yuval Noah Harari's theory of intersubjective fiction, John Searle's institutional facts, Robert Shiller's narrative economics, and Robert Stanton's structuralism, this qualitative study aims to reveal how Bitcoin is constructed as a collective belief system in Indonesia. Data were collected through the documentation of verbal transcripts and screenshots of visual elements. The findings indicate that Bitcoin is constructed as a protagonist character ("Gold 2.0") legitimized by global and local institutional validators, whereas altcoins are personified as antagonists. The narrative setting is constructed through temporal (halving), scientific (Stock-to-Flow and Bitcoin Clock), macroeconomic, and emotional dimensions. The narrative plot is arranged persuasively and adaptively, moving from debunking profit myths and accumulating empirical evidence to reaching a climax in a generational outlier event and concluding with a practical resolution. In conclusion, the high rate of Bitcoin adoption in Indonesia is driven not merely by technical-economic factors, but by the effectiveness of digital communication in maintaining a consistent intersubjective fiction across various market conditions. This study contributes to the literature on digital media discourse and financial narrative framing.Penelitian ini menganalisis konstruksi naratif Bitcoin pada kanal YouTube Angga Andinata melalui dua video sampel yang mewakili fase pasar berlawanan, yaitu Halving 2024: Ini Jalan Ninjaku (fase bull market) dan Bocoran Bottom Bitcoin 2026 (fase bear market). Mengintegrasikan teori fiksi intersubjektif Yuval Noah Harari, fakta institusional John Searle, narrative economics Robert Shiller, serta strukturalisme Robert Stanton, penelitian kualitatif ini bertujuan mengungkap bagaimana Bitcoin dikonstruksi sebagai sistem kepercayaan kolektif di Indonesia. Data dikumpulkan melalui dokumentasi transkripsi verbal dan tangkapan layar elemen visual. Temuan menunjukkan bahwa Bitcoin dikonstruksi sebagai karakter protagonis (Gold 2.0) dengan legitimasi validator institusional global maupun lokal, sedangkan altcoin dipersonifikasikan sebagai antagonis. Latar narasi dibangun melalui dimensi temporal (halving), saintifik (Stock to Flow dan Bitcoin Clock), makroekonomi, serta emosional. Alur narasi disusun secara persuasif dan adaptif, bergerak dari pembongkaran mitos keuntungan, penumpukan bukti empiris, klimaks peristiwa generasional (outlier event), hingga resolusi practical. Kesimpulannya, tingginya adopsi Bitcoin di Indonesia tidak hanya didorong faktor ekonomi teknis, melainkan oleh efektivitas komunikasi digital dalam memelihara fiksi intersubjektif yang konsisten di berbagai kondisi pasar. Penelitian ini berkontribusi pada kajian wacana media digital dan narrative framing finansial.